Penetration and Pullout Capacity of Low-Skirted Suction Caissons - Mingyuan Wang; Xiaoke Liu; Xinglei Cheng; Qun Lu; Jiaqing Lu; Miao Wang (Shock and Vibration)
The bearing capacity of suction caissons is the key to the design of offshore structures. A new type of cross-shaped low-skirted suction caisson is invented to effectively improve the bearing capacity, considering inevitable “soil plug” phenomenon. The behaviors of penetration and pullout for new low-skirted suction caisson are investigated by performing model tests. A new formula for calculating the penetration resistance is suggested based on the limit equilibrium theory and the test data, which can consider the change of the lateral area of the suction caisson during penetration. The behaviors of low-skirted suction caisson under inclined loading are analyzed by carrying out finite element simulation. The effects of loading angles and loading positions on the ultimate bearing capacity and failure mechanism of low-skirted suction caissons are discussed. The research results can provide a reference for the design of suction bucket foundation for offshore structures.